An archaeal CRISPR type III-B system exhibiting distinctive RNA targeting features and mediating dual RNA and DNA interference. Issue 1 (10th December 2014) - Peng, Wenfang; Feng, Mingxia; Feng, Xu; Liang, Yun Xiang; She, Qunxin
Abstract : CRISPR-Cas systems provide a small RNA-based mechanism to defend against invasive genetic elements in archaea and bacteria. To investigate the in vivo mechanism of RNA interference by two type III-B systems (Cmr-α and Cmr-β) in Sulfolobus islandicus, a genetic assay was developed using plasmids carrying an artificial mini-CRISPR (AC) locus with a single spacer. After pAC plasmids were introduced into different strains, Northern analyses confirmed that mature crRNAs were produced from the plasmid-borne CRISPR loci, which then guided gene silencing to target gene expression. Spacer mutagenesis identified a trinucleotide sequence in the 3′-region of crRNA that was crucial for RNA interference. Studying mutants lacking Cmr-α or Cmr-β system showed that each Cmr complex exhibited RNA interference. Strikingly, these analyses further revealed that the two Cmr systems displayed distinctive interference features. Whereas Cmr-β complexes targeted transcripts and could be recycled in RNA cleavage, Cmr-α complexes probably targeted nascent RNA transcripts and remained associated with the substrate. Moreover, Cmr-β exhibited much stronger RNA cleavage activity than Cmr-α. Since we previously showed that S. islandicus Cmr-α mediated transcription-dependent DNA interference, the Cmr-α constitutes the first CRISPR system exhibiting dual targeting of RNA and DNA.